Microplastic Degradation using Laccase Enzyme from Trametes hirsuta: In the Silico Study - Riyanto, Hanzhola Gusman; Sylvia, Diana (UI Scholars Hub, 2025)
Microplastics are a serious global problem that arises worldwide because of their widespread use. Exposure to microplastics can negatively affect human and environmental health. In this study, we used molecular docking methods with MOE software (version 2014.0901) to investigate the interaction between the laccase enzyme and several microplastic compounds as a preliminary study of microplastic degradation using enzymes. The Quantitative Structure Analysis Relationship (QSAR) analysis revealed that all microplastic ligands had higher Pa values than Pi, indicating that the laccase enzyme may be biologically active. The findings of the present study show that polyamide (PA) has the lowest binding energy among microplastics, implying that the enzyme can interact well with both active sites. In contrast, polypropylene exhibited the highest binding energy, indicating a lack of strong residue interactions between the ligand and the active sites. The Phe463 active site work well when dealing with nonpolar aromatic polymers, including polycarbonate, poly (methyl methacrylate), polystyrene, and polyurethane, allowing for significant π–π stacking interactions. The Ile455 active sites are more effective when dealing with polar aromatic polymers, such as PET and polyamide, due to their better hydrogen bonding or dipole interactions. This finding can be used as an initial basis for microplastic enzymatic degradation